Advancing Laboratory Medicine: A Review of Emerging Technologies and Their Impact on Diagnostic Accuracy and Efficiency - Alabdali, Dalal Hammad; Alsolami, Eman Aali; AlSehli, Ohood Obaidullah; Aldawsari , Haya Hamad; Alzain, Bayan Musa; Yamani, Omar Farooq; Alsharif, Ruwayda Nawaf; Endergiri , Duaa I. M.; AL- Harthi, Abdulhadi Saad; Alamoudi, Alaa Hassan (Journal of Ecohumanism, 2024)
Laboratory medicine plays a pivotal role in modern healthcare, serving as the backbone of diagnostic accuracy and patient management. However, traditional methods often face challenges such as manual errors, extended turnaround times, and limited scalability. This review explores the transformative impact of emerging technologies, including automation, artificial intelligence (AI), robotics, and digital pathology, on laboratory diagnostics. These innovations have not only enhanced diagnostic precision and reliability but have also significantly improved efficiency and throughput in clinical laboratories. Automation streamlines sample processing, while AI-driven tools enable advanced data analysis and predictive modeling. Robotics and digital imaging contribute to precision and accessibility, revolutionizing high-throughput environments and remote diagnostics. Despite the promising advancements, challenges such as high implementation costs, the need for specialized training, and ethical considerations remain. This review provides a comprehensive analysis of these technologies, highlighting their benefits, current applications, and future potential in shaping a more accurate, efficient, and patient-centered laboratory medicine landscape.